Moral Intelligence and its Relation to Conflict Resolution Skill among King Saud University Students in the light of some Variables - Ali Mousa Suliman Aalsubhien; Mohammad Farhan Alqudah; Alhemaidi Mohammed Aldhaidan; Abdullah Khretan Alenazi; Mustafa Heilat (University of Science and Technology, Yemen, 2019)
The aim of the present study was to identify moral intelligence and its relation to conflict resolution skill among King Saud University students in the light of gender, the type of college (sciences or humanities) and the study level. Furthermore, this study attempted to find out whether it is possible to predict the conflict resolution skill among students of King Saud University (KSU) by their score on the moral intelligence scale. The sample of the study consisted of (360) students from KSU. The researchers used the correlative and comparative descriptive method. The findings of the study indicated that the score of the moral intelligence and conflict resolution skill was low. In addition, the findings showed that there was a difference in moral intelligence in favor of males, while there were no statistically significant differences in the moral intelligence based on the type of college or the study level. The study findings also revealed that there was a statistically significant correlation at the level of 0.01 between moral intelligence and conflict resolution skill. It was also found out that independent variables (dimensions of moral intelligence: sympathy, conscience, recognition of emotions & moral imagination) contribute to predicting the overall skill of conflict resolution. Keywords: conflict resolution, moral intelligence, KSU, KSA.